Utilizing multiple funding avenues to develop necessary infrastructure in James Irrigation District - Hopkins, Joseph D., author; Ehlers, Brian E., author; Mallyon, John, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
Due to multiple impacts being placed on the James Irrigation District (District) water supply, a study was performed to understand if the District could sustain its current operations. It was determined that the practices could continue but it would require capitally intensive improvements to the Districts infrastructure. Planned improvements include the construction of recharge basins for sustainability, installation of up to 16 groundwater wells and pumps, basin construction, pipeline installation, and construction of flow control and pumping structures. The improvements were estimated to cost approximately $9,000,000; a cost too high for the District to fund on their own. Because of the urgency of the project, The District explored multiple opportunities to fund the project. This included applying for loans, applying for grants, raising water rates, and raising land assessments; all at the same time. To obtain loan money the District applied for funds through Proposition 82, distributed by the Department of Water Resources (DWR). At this same time, the district pursued loans through local banks, which provided a challenge considering the unstable banking industry. Many components of the project are proposed to be built using grant funding. First was a Challenge Grant as provided by United States Bureau of Reclamation's (USBR) Water 2025 program; providing $300,000. Next was the USBR Field Services program; providing $25,000. Approximately $50,000 was utilized from the DWR Local Groundwater Assistance Program. In addition to these funds, Recovery Act funding became available for drought relief, where the District could obtain roughly $1,500,000. To generate further income the District approved a water rate increase. It was at this time when it became apparent that the Districts revenue source had become out of balance. The Land assessments were not enough to cover the operational overhead of the District. To rectify this issue, land assessments would need to be raised. This would require a proposition 218 election, which has been pursued. The intention of this paper is to discuss the multiple funding sources available to the District, how they were utilized, and problems that have been encountered.
USCID water management conference
Presented at Upgrading technology and infrastructure in a finance-challenged economy: a USCID water management conference held on March 23-26, 2010 in Sacramento, California.